THE EFFECT OF AVERRHOA BILIMBI EXTRACT AS NATURAL COAGULANTS ON THE CHARACTERISTICS OF RUBBER - Feerzet Achmad; Deviany Deviany (Universitas Lambung Mangkurat, 2022)
Rubber is one of Indonesia’s main commodities resulting in a considerable number of people relying their incomes as rubber farmers. However, unstable rubber price proves to be a problem for these farmers. One solution to be offered is an alternative natural coagulant which is easily obtainable and able to produce good quality rubbers. Averrhoa bilimbi with its known acidic properties shows a prospect as a natural coagulant. This study aims to determine the effect of variation in the concentration of Averrhoa bilimbi extract on the characteristics of rubber clone IRR 118 as well as the advantages and disadvantages of using the extract as natural coagulant. The rubber clone used was IRR 118 with various Averrhoa bilimbi etracts of 20%, 40%, 60%, 80% and 100% and 2% synthetic chemical coagulant formic acid as comparison. The coagulant volume was 20 ml for each concentration and the volume of latex used was 100 ml. The characteristics of the rubber tested were TSC, DRC, Po and PRI. The results showed that the highest value of dry rubber content (DRC) was at 100% natural coagulant concentration which is 34% with a total solid content (TSC) value of 37% while the highest Plasticity Retention Index (PRI) value was at 100% concentration, which is 92%. This study exhibits the use of natural coagulant from Averrhoa bilimbi has met the Indonesian Rubber Standard SNI 06-1903-2000. Therefore, Averrhoa bilimbi extract can be used as an alternative coagulant for rubber latex.